ID1 marks the tumorigenesis of pancreatic ductal adenocarcinoma in mouse and human - Yuanxin Tang; Sheng Zhang; Jiazi Li; Chunli Wu; Qing Fan (Scientific Reports, 2022)
Abstract Pancreatic Ductal Adenocarcinoma (PDAC) is a deadly disease that has an increasing death rate but no effective treatment to now. Although biological and immunological hallmarks of PDAC have been frequently reported recently, early detection and the particularly aggressive biological features are the major challenges remaining unclear. In the current study, we retrieved multiple scRNA-seq datasets and illustrated the genetic programs of PDAC development in genetically modified mouse models. Notably, the transcription levels of Id1 were elevated specifically along with the PDAC development. Pseudotime trajectory analysis revealed that Id1 was closely correlated with the malignancy of PDAC. The gene expression patterns of human PDAC cells were determined by the comparative analysis of the scRNA-seq data on human PDAC and normal pancreas tissues. ID1 levels in human PDAC cancer cells were dramatically increased compared to normal epithelial cells. ID1 deficiency in vitro significantly blunt the invasive tumor-formation related phenotypes. IPA analysis on the differentially expressed genes suggested that EIF2 signaling was the core pathway regulating the development of PDAC. Blocking EFI2 signaling remarkably decreased the expression of ID1 and attenuated the tumor-formation related phenotypes. These observations confirmed that ID1 was regulated by EIF2 signaling and was the critical determinator of PDAC development and progression. This study suggests that ID1 is a potential malignant biomarker of PDAC in both mouse models and human and detecting and targeting ID1 may be a promising strategy to treat or even rescue PDAC.